Analysis of the grounds for the emergence of obligations from unjust enrichment in modern Kazakh civil law (Journal of actual problems of jurisprudence, 2018)
In тhis article discusses the questions of the origin of obligations from unjust enrichment in the civil law. One type of non-contractual enforcement of obligations in the civil law – obligations due to unjust enrichment with the purpose of protecting the property. To date, the lack of uniform understanding and approach to fundamental problems of legal relationship of unjust enrichment, ambiguity in legal practice, strengthening the process of improving the legislation, together determine the relevance of the proposed to the reader article.Key words: obligation, unjust enrichment, acquisition, conservation, transferee, victim, legal facts.